Rapid weight loss and the body fluid balance and hemoglobin mass of elite amateur boxers - Reljic, D.; Hässler, E.; Jost, J.; Friedmann-Bette, B. (Journal of Athletic Training, 2013)
Context: Dehydration is assumed to be a major adverse effect associated with rapid loss of body mass for competing in a lower weight class in combat sports. However, the effects of such weight cutting on body fluid balance in a real-life setting are unknown. Objective: To examine the effects of 5% or greater loss of body mass within a few days before competition on body water, blood volume, and plasma volume in elite amateur boxers. Design: Case-control study. Setting: Sports medicine laboratory. Patients or Other Participants: Seventeen male boxers (age = 19.2 ± 2.9 years, height = 175.1 ± 7.0 cm, mass = 65.6 ± 9.2 kg) were assigned to the weight-loss group (WLG; n = 10) or the control group (CON; n = 7). Intervention(s): The WLG reduced body mass by restricting fluid and food and inducing excessive sweat loss by adhering to individual methods. The CON participated in their usual precompetition training. Main Outcome Measure(s): During an ordinary training period (t-1), 2 days before competition (t-2), and 1 week after competition (t-3), we performed bioelectrical impedance measurements; calculated total body water, intracellular water, and extracellular water; and estimated total hemoglobin mass (tHbmass), blood volume, and plasma volume by the CO-rebreathing method. Results: In the WLG, the loss of body mass (5.6% ± 1.7%) led to decreases in total body water (6.0% ± 0.9%), extracellular water (12.4% ± 7.6%), tHbmass (5.3% ± 3.8%), blood volume (7.6% ± 2.1%; P < .001), and plasma volume (8.6% ± 3.9%). The intracellular water did not change (P > .05). At t-3, total body water, extracellular water, and plasma volume had returned to near baseline values, but tHbmass and blood volume still were less than baseline values (P < .05). In CON, we found no changes (P > .05). Conclusions: In a real-life setting, the loss of approximately 6% body mass within 5 days induced hypohydration, which became evident by the decreases in body water and plasma volume. The reduction in tHbmass was a surprising observation that needs further investigation.